A expressão da dimensão educativa no trabalho do assistente social na política de assistência social - Ligabue, Helena de Paiva [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
O presente trabalho objetiva investigar a expressão da dimensão educativa do Serviço Social na política de assistência social. Pretende estudar como a função pedagógica inerente ao trabalho do assistente social tem se efetivado nos Centros de Referência de Assistência Social (CRAS), considerando essa dimensão imersa no conceito de instrumentalidade do Serviço Social. Para tanto foi realizado um debate teórico sobre as seguintes categorias inerentes aos objetivos desse trabalho: dimensão educativa do Serviço Social; instrumentalidade do Serviço Social; trabalho profissional; e política de assistência social. E uma investigação em pesquisa de campo, buscando compreender a visão dos assistentes sociais acerca da dimensão educativa materializada em seus trabalhos no CRAS, em quais perspectivas se realiza essa dimensão, e a visão do profissional sobre como a Politica Nacional de Assistência Social (PNAS) tem orientado a função pedagógica do Serviço Social no CRAS.

This dissertation intents to investigate the expression of educational dimension of Social Work in the social assistence policy. Intents to study how the pedagogy function, inherent at the functions of social worker, has been applied in the “CRAS- Centro de Referência de Assistência Social” (Social Assistance Reference Centers), considering this dimension as immersed in the concept of instrumentality of Social Work. For this purpose has been made a theoretical debate about the following categories inherent to the objectives of this thesis: educational dimension of Social Work, instrumentality of Social Work; professional work; and social assistence policy. Also, a research in the field in order to understand the comprehension of social workers about the educational dimension materialized in their functions at the CRAS, in which perspectives this dimension is realized and the comprehension of social worker about how national social assistence policy has been guiding the pedagogy function of Social Work in the CRAS.
The expression of the educational dimension in the work of the social worker in the policy of social assistence
Keywords: Dimensão educativa do serviço social; Instrumentalidade do serviço social; Trabalho profissional; Política de assistência social; Educational dimension of social work; Instrumentality of social work; Professional work; Social assistence policy